AB0835 More severe expression of systemic sclerosis in men than women from an ethnic cohort followed at a single center. (23rd January 2014) - Panopoulos, S.; Bournia, V.K.; Giavri, I.; Fragiadaki, K.; Vlachoyiannopoulos, P.; Sfikakis, P.P.
Abstract : Background: Whether systemic sclerosis (SSc) is differently expressed in men versus women has been debated. This is probably due to the fact that published information mainly derives from multi-ethnic cohorts followed at tertiary care centers, which always include patients referred for severe disease. In these cohorts the men/women ratios are higher (1/4-5) compared to ethnic cohorts (1/7-9), suggesting biases in the former cohorts due to under-representation of women with milder forms of SSc. Objectives: To search for possible differences in morbidity and mortality between men and women with SSc who belong to an ethnic cohort followed at a single academic centre. Methods: Demographic, clinical, and outcome data from all SSc patients who had been examined between 1995 and 2011 in our Department were retrospectively analysed. For the purpose of the present study, non-Greek patients referred to our centre were excluded. In order to identify differences in clinical expression, all disease manifestations present in consecutive 3-year intervals from disease onset were recorded for each patient. Independent sample t-tests and Kaplan-Meier analyses were used to search for possible differences between men and women. Results: The men/women ratio was 1/8.7 in a total of 223 patients. At the time of last evaluation the mean±SD age in men and women was 55±15 and 59±14 years, while disease duration was 9±7 and 13±10 years, respectively. Age at SSc onset (46±15 in men; 46±15 in women), diffuse skin involvement (61.3% in men; 46.4% in women) and Scl70 positivity (66.6% in men; 59.2% in women) were not significantly different between genders. Prevalence of interstitial lung disease, upper and lower gastrointestinal disease, echocardiographic findings, including estimation of pulmonary artery pressure, and joint contractures during the first through the fourth 3-year interval from disease onset were also not different. However, vasculopathy occurred earlier in men than women, since in the first three years after disease onset digital ulcers and renal crisis developed in 54 vs 31% (p=0.036) and 17 vs 3% (p=0.006), respectively. After excluding non-SSc related deaths, survival was significantly worse in men compared to women (88 vs 99% at 3 years, p=0.001; 80 vs 98%, at 6 years p=0.001; 67 vs 93%, p=0.003 at 6 years and 58 vs 91% at 12 years, p=0.002, respectively). Kaplan-Meier analysis confirmed the worse survival of men with SSc over women (Mantel-Cox test, p=0.002). No significant differences were identified between men and women regarding social history, including smoking, past medical history, including hypertension, or disease management, including immumomodulatory regimens and endothelin receptor antagonist. Conclusions: These results, derived from a patient cohort which is representative of the SSc population in Greece, show that the clinical expression of the disease is more severe in men. Further studies to confirm that SSc-associated vasculopathy may develop earlier in men than women are warranted. Disclosure of Interest: None Declared